Increased Stiffness of the Superficial Cervical Extensor Muscles in Patients With Cervicogenic Headache: A Study Using Shear Wave Elastography - Lin, Li-Zhen; Yu, Yan-Ni; Fan, Jie-Cheng; Guo, Pei-Wu; Xia, Chun-Feng; Geng, Xue; Zhang, Shu-Yun; Yuan, Xiang-Zhen (Frontiers in Neurology, 2022)
Background: Cervicogenic Headache (CEH) is a secondary headache caused by the lesions of cervical spine and surrounding soft tissues. Cervical muscle dysfunction may be related to the onset of CEH. However, whether cervical muscle stiffness changes in CEH patients has not been well studied. The purpose of this study was to explore the changes of superficial cervical extensor stiffness in CEH patients using shear wave elastography (SWE). Methods: Nineteen CEH patients and 20 healthy controls were recruited for the study. The stiffness of superficial cervical extensor muscles was obtained from SWE, and a SL10-2MHz linear array probe in musculoskeletal muscle mode was chosen as transducer. Regions of interest in trapezius (TRAP), splenius capitis (SPL), semispinalis capitis (SCap), and semispinalis cervicis (SCer) were manually segmented. The correlations between the stiffness of superficial cervical extensor muscles and visual analogue scale (VAS) scores, age, and Body Mass Index were analyzed using Pearson correlation. Receiver operating characteristic curve was used to investigate the diagnostic ability of superficial cervical extensor stiffness for CEH. Results: The stiffness of superficial cervical extensor muscles on headache side of CEH patients was higher than that on non-headache side and healthy controls (P<0.05). Increased stiffness was also observed in SCer on the non-headache side of CEH patients compared to healthy controls (P<0.01). In CEH patients, the stiffness of SCer was positively correlated with VAS scores (r=0.481, P=0.037), but no correlation was found between other muscles and VAS scores (P>0.05). The areas under the curve of TRAP, SPL, SCap, and SCer in diagnosing CEH were 0.766, 0.759, 0.964, and 1.000, respectively. Conclusions: Increased stiffness was observed in superficial cervical extensor muscles on the headache side of CEH patients. The stiffness of SCer was correlated with the headache intensity in CEH patients and may provide clues for the diagnosis of CEH.